PRIVILEGE UMAT NABI MUHAMMAD SAW MENURUT PANDANGAN IBNU KATSIR (STUDI PENAFSIRAN SURAT ALI IMRON :110) - Jauharotul Humairoh; Moch. Nurcholish (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Muslims are the luckiest people because they are given grace in the form of the sending of khatim al-Anbiya', namely the Prophet Muhammad who because of the existence of all creatures on earth were created including the prophet Adam A.S. in addition to being destined to be the people of the Prophet, we are blessed with several privileges that Allah has never given to the previous servants, this is not spared because of the blessing of the Prophet Muhammad who lobbies to us. Among these privileges are the praise and reward of Allah for carrying out His commands, amar ma'ruf nahi munkar and believing in Allah is the key to getting his reward as "Khoiroh Ummah" because these three are principles that are upheld by Allah for this ummah in forming Ukhuwah Islamiyah. This research is classified as Library Research because it uses data in a descriptive analytical manner. The research style of Tafsir Ibn Kathir has a suitable method to be used as the main source in revealing the secrets of the verses of the Qur'an which tell that the people of the prophet Muhammad are the best people, The results of this research show that Ibn Kathir's interpretation has an objective explanation in interpreting Ali Imron:110, namely the existence of amar ma'ruf nahi munkar as well as faith in Allah as the cause of being given the title "the best of the people".